A Review on the Milestones of Blue Light-Emitting Materials in India - Odedara, Nisha; Borane, Niteen; Patel, Rahul; Boddula, Rajamouli (Organic Materials, 2023)
Since 1987 in the field of optoelectronics, organic light-emitting diodes (OLEDs) have secured their position because of their extreme use in panels of lighting applications such as TV and smartphone displays. At present, OLEDs are at top-notch position in the lighting market for their promising features. The field of OLEDs is rapidly growing day by day in academia and industry due to the success of OLEDs in the form of excellent efficiency, feasible methods, excellent lifetime, color purity, and superb device architecture. As a result, OLEDs are new profitable leading devices of the 21st century. However, the OLED industry has evolved in optoelectronics in the last 30 years and is advancing rapidly just because of the development in OLED materials (fluorescent, phosphorescent, thermally activated delayed fluorescent, and blue light-emitting materials). Blue light-emitting materials have achieved incredible popularity nationally and internationally. At the international level, USA, Japan, Korea, and Germany are at the top of the list in the production of OLEDs. India has also seen rapid progress in OLED development in the last 12 years and details of research in blue OLEDs by key players of India are involved in this report.1 Introduction1.1 OLED Construction1.2 Working of OLED2 OLED Development2.1 Historical Background of OLED2.1.1 International Status2.1.2 National Status3 Progress of Blue Emitters in India4 Present Scenario of Blue OLEDs5 Conclusions and Outlook
Keywords: optoelectronics; blue emitters; organic materials